2018
DOI: 10.1148/radiol.2018171139
|View full text |Cite
|
Sign up to set email alerts
|

Female Human Spines with Simulated Osteolytic Defects: CT-based Structural Analysis of Vertebral Body Strength

Abstract: Purpose To evaluate a CT structural analysis protocol (SAP) for estimating the strength of human female cadaveric spines with lytic lesions. Materials and Methods Osteolytic foci was created in the middle vertebra of 44 thoracic and lumbar three-level segments from 11 female cadavers (age range, 50-70 years). The segments underwent CT by using standard clinical protocol and their failure strength was assessed at CT SAP. The spines were mechanically tested to failure in pure axial compression or in compression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Cavities or lesions can remain in the healed vertebral bodies, as observed in figures from previously reported studies in the literature [9,[11][12][13]. Given that focal regions of bone loss have been proven to reduce the structural competence of vertebrae, these cavity lesions may be significantly related to the recurrence of vertebral collapse after implant removal [14][15][16]. Furthermore, the impact of a lesion on the structural properties of the vertebral body is related to its size and location [16].…”
Section: Introductionmentioning
confidence: 88%
“…Cavities or lesions can remain in the healed vertebral bodies, as observed in figures from previously reported studies in the literature [9,[11][12][13]. Given that focal regions of bone loss have been proven to reduce the structural competence of vertebrae, these cavity lesions may be significantly related to the recurrence of vertebral collapse after implant removal [14][15][16]. Furthermore, the impact of a lesion on the structural properties of the vertebral body is related to its size and location [16].…”
Section: Introductionmentioning
confidence: 88%
“…As part of a previous study 23 , 3-level segments (T6-T8, T9-T11, T12-L2, and L3-L5) were obtained from 8 fresh-frozen cadaver spines from female donors with a mean age (and standard deviation) of 57 ± 6.6 years (range, 47 to 69 years). Each segment underwent CT imaging (Aquilion 64; Canon Medical Systems) to inspect for existing pathology or fractures and compute vertebral bone mineral density 23 . Twenty-four segments were selected for kinematic assessment (n = 6 for each segment), the segments were dissected clean of musculature, and the cranial and caudal vertebrae were shallowly embedded in cement for mechanical testing 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Hence, defect size is not the only predictive factor for vertebral strength reduction. Defect location is also predictive, especially for vertebral segments including the pedicles or costovertebral joints [112,113,[115][116][117]. A previous study also showed that transcortical defects reduce the vertebral strength [116], meaning that defect type is also a factor to be considered.…”
Section: Vertebral Fracture Risk Assessment Using Numerical Simulationmentioning
confidence: 99%
“…The experimental studies investigating the influence of the defect size on the vertebral strength have drawn conflicting results. In some cases, defect size was considered as a predictive factor of vertebral strength [109][110][111], while the opposite has been reported in other studies [112][113][114]. Hence, defect size is not the only predictive factor for vertebral strength reduction.…”
Section: Vertebral Fracture Risk Assessment Using Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation